Philological spheres of Polish psalters. From the state of ordering towards new research tasks - Koziara, Stanisław (Philology as the Ordering of Chaos: Language and Text Studies. Ad honorem Professoris Marci Cybulski, 2018)
This paper concerns chosen philological items in the Polish psalter-biblical literature, which has been regularly affirmed in the history of Polish language from the Old Polish to contemporary usage. This work is an attempt at considering synthetically: 1) specific properties and cultural significance of biblical psalmody, 2) the phenomenon of many centuries of its presence in the Polish language, 3) the state and directions of previous linguistic research into national psalter heritage, as well as 4) it aims to point out new options and the need for new descriptions, which use less popular examples of national psalmody.